Xiaopiyishen Herbal Extract Granule Improves the Quality of Life among People with Fatigue-Predominant Subhealth and Liver-Qi Stagnation and Spleen-Qi Deficiency Syndrome - Xiao-lin Xue (Evidence-Based Complementary and Alternative Medicine, 2012)
To observe the effects of Xiaopiyishen Herbal Extract Granule (XPYS-HEG) on the quality of life in people with fatigue-predominant subhealth (FPSH) and liver-qi stagnation and spleen-qi deficiency syndrome, the participants were allocated randomly to the treatment group (XPYS, n=100) and the control group (placebo, n=100) in this study. The study period was 18 weeks (6 weeks for the intervention and 12 weeks for followup). The results show that there were no differences between the two groups for the scores of eight factors on the SF-36 (Chinese version of the SF-36 universal quality-of-life scale) at baseline. Compared with the baseline score, intervention with XPYS-HEG led to a significant increase in scores for the factor of bodily pain at the end of the 6th week. Compared with the score at the end of the 6th week, the score for the factor of mental health in the XPYS group significantly increased at the end of the 18th week. Therefore, XPYS-HEG could partially improve the quality of life for people with FPSH and liver-qi stagnation and spleen-qi deficiency syndrome, which can ease bodily pain, stimulate a positive mood, and ease a negative mood.